Minorities matter Malaysian politics and people - Lemiere, Sophie (Strategic Information and Research Development Centre ISEAS, 2020)
Bringing together a group of both international and Malaysian scholars, Minorities Matter: Malaysian Politics and People Volume III, is the third instalment in the 'Malaysian Politics and People' series, a series which has tracked Malaysian politics and society from the outcome of GE12 to the present day. Published in the aftermath of the fall of the BN government, Minorities Matter looks at the contemporary situation of Malaysian politics and society with a particular focus on those who are often left out of the national narrative, minorities, to understand the ways in which minority groups, from women to East Malaysians, the Orang Asli, refugees and more, have contributed towards, and been affected by, political change in Malaysia. With a particular focus on the problem of political culture, Minorities Matter highlights both the political and social changes, as well as continuities, witnessed since the 14th General Election highlighting, through the lens of minority groups, the contemporary contestations which now dominate Malaysian politics.